2000
DOI: 10.1111/j.1365-2133.2000.03711.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the vehicle on the synthesis of porphyrins after topical application of 5-aminolaevulinic acid. Implications in cutaneous photodynamic sensitization

Abstract: These findings reinforce the importance of the vehicle in topical ALA-based PDT, and explain the mechanism of action of DMSO in enhancing protoporphyrin IX biosynthesis in superficial lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 22 publications
0
27
1
Order By: Relevance
“…This is especially a problem in ALA-PDT. It is likely that poor response of BCCs, particularly nodular lesions to ALA-PDT, arises from an insufficient concentration of topical ALA achieved at approximately 2 mm from the surface of the lesion [24,44].…”
Section: Discussionmentioning
confidence: 99%
“…This is especially a problem in ALA-PDT. It is likely that poor response of BCCs, particularly nodular lesions to ALA-PDT, arises from an insufficient concentration of topical ALA achieved at approximately 2 mm from the surface of the lesion [24,44].…”
Section: Discussionmentioning
confidence: 99%
“…[4] Consequently, the penetration depth of ALA in intact skin is low, typically 1-2 mm. [5,6] Unsurprisingly, reports of ALA PDT for treatment of surface lesions describe long application times and formulations with high drug loadings. Times ranging from 2 to 6 h [7] and loadings of 10-30% (w/w) in a cream, ointment or gel formulation are commonplace.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that DMSO can improve the accumulation of PpIX in cell lines (Malik et al, 1995). Employing ALA plus DMSO in vivo in a transplantable murine adenocarcinoma, Casas et al (2000) have found a higher porphyrin accumulation in the skin overlying the tumour tissue and in the first 2 mm of tumour.…”
mentioning
confidence: 91%